Efektivitas Hambatan Ekstrak Etanol Daun Muda, Tua dan Sangat Tua Bambu Surat (Gigantochloa pseudoarundinacea) terhadap Bakteri Streptococcus pyogenes - Mamay; Nugraha, Yogi Rahman; Mulya Ulfah, Sri (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Streptococcus pyogenes is a pathogenic bacterial upper respiratory tract that cause various diseases, and the most common cause of bile pharyngitis. This bacteria has a sensitivity to penicillin G. This study aims to determine differences of inhibition effectiveness of ethanol extract of green leaves, ripe and very ripe greater giant bamboo (Gigantochloa pseudoarundinacea) to Streptococcus pyogenes bacteria Method: This type of research is experimental research with the Kirby Bauer method. The treatment group used paper discs that had been diffused from the ethanol extract of young, old and very old leaves of bamboo at a concentration of 100% on Mueller Hinton Agar media that had been planted with Streptococcus pyogenes Result: The inhibition zone obtained from extracts of young leaves was 0.28 mm, old leaves were 11.40 mm, very old leaves were 11.80 mm Conclusion The effectiveness inhibition of Streptococcus pyogenes bacterial growth for the ethanol extract of young bamboo leaves was classified as weak, the ethanol extract for old and very old leaves was classified as strong. Suggestions for further research, for selecting good leaves are very old leaves and using a different solvent for extraction solvents.